Exploring Challenges of Web-Based Purchasing - Nadesan, Santhia; Choo, Wou Onn; Sorooshian, Shahryar (Blue Eyes Intelligence Engineering & Sciences Publication, 2019)
The main goal of the current article was to review challenges of online purchasing. Theoretically, this research has few benefits and has importance which the findings of this study will listing the crucial challenges that need to be addressed and tackled to achieve the success of E-commerce (and precisely electronic-shopping) in companies. It encourages additional utilization of technologies of Electronic-Commerce, styles the e-transaction practice at ease, boosts the amount of acknowledgement and adoption of this online technology, results in advancement of online customer responsibility, presents the loyalty concept, raise customer satisfaction, sustains longer-term relationship with clienteles and contributions to obtaining of competitive advantages.